German Jews : a dual identity - Mendes-Flohr, Paul R. (New Haven, Conn. : Yale University Press, 1999)
In this book the author explores through the prism of Rosenweig's image of how German Jews have understood and contended with their two-fold spiritual patrimony. He deepens the discussion to consider also how the German-Jewish experience bears upon the general random experience of living with multiple cultural identities.
The bifurcated soul of the German Jew -- History and kultur: the German-Jewish perspective -- The German-Jewish Parnassus -- Franz Rosenzweig's Eulogy for German Jewry -- Epilogue: reflections on the legacy of German Jewry.
Includes bibliographical references (pages 97-140) and index.
Print version record.
English.
JSTOR
Keywords: Rosenzweig, Franz, -- 1886-1929.; Rosenzweig, Franz, -- 1886-1929; Jews -- Germany -- Identity; Jews -- Cultural assimilation -- Germany; Germany -- Ethnic relations; Juifs -- Allemagne -- Identité.; Juifs -- Acculturation -- Allemagne; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; HISTORY -- Jewish; Ethnic relations; Jews -- Cultural assimilation; Jews -- Identity; Germany; Joden; Identiteit; Duitsland